2016
DOI: 10.1111/birt.12245
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Promoting Hospital Primary Vaginal Birth: A Qualitative Study

Abstract: Caregivers and first-time mothers identified early labor management and childbirth preparation as important factors to promote primary vaginal birth in hospital settings. Both deserve further inquiry as potential strategies to decrease rising cesarean delivery rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…Four further studies were identified by key informants and through back-chaining reference lists. [27,29,40,61] (Fig 1) Nineteen studies were graded A or B for quality. Five were graded C, and one D. Of the 25 studies, nine were from high-income countries, five from Africa, four from Latin America, three from China, two from Iran, one from Bangladesh and one from Lebanon.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four further studies were identified by key informants and through back-chaining reference lists. [27,29,40,61] (Fig 1) Nineteen studies were graded A or B for quality. Five were graded C, and one D. Of the 25 studies, nine were from high-income countries, five from Africa, four from Latin America, three from China, two from Iran, one from Bangladesh and one from Lebanon.…”
Section: Resultsmentioning
confidence: 99%
“…The studies investigated stakeholder views of different types of midwife staffing models [36,50,5254]; financial strategies [28,29,43–44,48,5860]; and organisational culture [27,40,42,46,47,49,51,55–57,61,62]. We also included two studies of social (doula) support during labour [39,41], with the decision for inclusion made by consensus, because of their positive effect on caesarean section rate reduction in the associated Cochrane review of effectiveness studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations